Analysis of Shrinkage Defect in Sand Casting by Using Six Sigma Method with Taguchi Technique. Issue 1 (February 2021) - Omprakas, M A; Muthukumar, M; Saran, S P; Ranjithkumar, D; Shantha kumar, C M; Thiruppathi Venkatesh, S; Sengottuvelan, M
Abstract: Casting industries play a major role in the field of manufacturing. The production of complex shape and size products is manufactured in a single process, which cannot be produced in other manufacturing processes. Because the other process needs more than one step to convert a raw material into a product. When producing the casting, the quality of the casting should be maintained without defects. This is not possible as we can't produce a cent percentage of accuracy. But the percentage of defects can be reduced with the help of certain quality control tools and techniques. In this paper, the main focus is to reduce the shrinkage defect which occurs in the External Bearing Ring of ductile cast iron which is produced in the leading casting industry in Coimbatore. The data have been collected from the industry for the six months and the defects have been identified with the help of the Six-Sigma DMAIC (Define, Measure, Analyze, Improve, Control) technique. The quality control tools are applied in different stages of the DMAIC technique for identifying and controlling the defects. Also, the Taguchi technique is applied for creating the L9 orthogonal array from the Minitab software. Finally, the best possible solution is obtained and it is suggested to the industry for defects reduction.